Recurrence and progression of periodontitis and methods of management in long‐term care: A systematic review and meta‐analysis. (10th November 2021) - Leow, Natalie M.; Moreno, Federico; Marletta, Debora; Hussain, Syed Basit; Buti, Jacopo; Almond, Neil; Needleman, Ian
Abstract: Aim: To systematically review the literature to evaluate the recurrence of disease of people in long‐term supportive periodontal care (SPC), previously treated for periodontitis, and determine the effect of different methods of managing recurrence. The review focused on stage IV periodontitis. Materials and methods: An electronic search was conducted (until May 2020) for prospective clinical trials. Tooth loss was the primary outcome. Results: Twenty‐four publications were retrieved to address recurrence of disease in long‐term SPC. Eight studies were included in the meta‐analyses for tooth loss, and three studies for disease progression/recurrence (clinical attachment level [CAL] loss ≥2 mm). For patients in SPC of 5–20 years, prevalence of losing more than one tooth was 9.6% (95% confidence interval [CI] 5%–14%), while experiencing more than one site of CAL loss ≥2 mm was 24.8% (95% CI 11%–38%). Six studies informed on the effect of different methods of managing recurrence, with no clear evidence of superiority between methods. No data was found specifically for stage IV periodontitis. Conclusions: A small proportion of patients with stage III/IV periodontitis will experience tooth loss in long‐term SPC (tendency for greater prevalence with time). Regular SPC appears to be important for reduction of tooth loss. No superior method to manage disease recurrence was found.